Administrative And Demographic Structures of Keban’s Villages In the First Half 19th Century - Çakar, Enver (Fırat University, 2019)
In this study, the administrative and demographic structure of the villages of Keban district in the first half of the 19th century was investigated by using the Ottoman population records as a source.Today, Keban is a district center connected to the province of Elazig. Keban was conquest by the Ottomans in 1515 and managed as a district (nahiya) subject to Çemişgezek for a long time.Having lead and silver reserves, Keban became increasingly important in the Ottoman Empire from the beginning of the 18th century when these mines began to be removed. In parallel with this increase in importance, Maadin-i Hümayun Emaneti was established in 1775, and Keban town has increased to the central position of this administration. In addition, many kadas (districts) around Keban have been included in the Maadin-i Hümayun Emaneti from financial and administrative perspectives.The villages of today's Keban district were administratively linked to Çemişgezek, Harput, Arapgir and Arguvan kadas. Although all of these villages were Muslim villages, there were very few non-Muslim populations in some of the villages. But in the second half of the 19th century, important changes were made to the administrative structure of the kadas that constituted Maadin-i Hümayun. Especially in the last quarter of the century when mining activities were ended, Arguvan was incorporated into Keban, which had been turned into a nuke by narrowing the borders with the numerous villages of Arapgir, Çemişgezek and Harput.

Bu çalışmada, Osmanlı nüfus defterleri kaynak olarak kullanılmak suretiyle, Keban ilçesi köylerinin 19. yüzyılın ilk yarısındaki idari ve demografik yapısı incelenmiştir.Bugün Elazığ iline bağlı bir ilçe merkezi olan Keban, 1515 yılında Osmanlı idaresine geçmiş ve uzun bir süre Çemişgezek Sancağı’na bağlı bir nahiye merkezi olarak varlığını sürdürmüştür.Kurşun ve gümüş rezervlerine sahip olan Keban, bu madenlerin çıkarılmaya başlandığı 18. yüzyılın başlarından itibaren Osmanlı Devleti içerisinde gittikçe önem kazanmıştır. Bu önemin artmasına paralel olarak, 1775 yılında Maadin-i Hümayun Emaneti kurulmuş, Keban Kasabası da bu emanetin merkezi konumuna yükselmiştir. Ayrıca Keban’ın çevresinde yer alan birçok kaza da mali ve idari açılardan Maadin-i Hümayun Emaneti’ne dâhil edilmiştir.19. yüzyılın ilk yarısında mahalle ve çarşılardan oluşan Keban, bir eyalet merkezi konumundaydı ve köyleri yoktu. Bugünkü Keban ilçesini oluşturan köyler ise, idari bakımdan Çemişgezek, Harput, Arapgir ve Arguvan kazalarına bağlıydı. Bu köylerin hepsi Müslüman köyleri olmakla birlikte, bazı mezralarında çok az sayıda gayrimüslim nüfus da barınmaktaydı. 19. yüzyılın ikinci yarısında Maadin-i Hümayun’u oluşturan kazaların idarî yapısında önemli değişiklikler yapılmıştır. Özellikle madencilik faaliyetlerinin sona erdirildiği yüzyılın son çeyreğinde, bundan önce Arapgir, Çemişgezek ve Harput kazalarına bağlı olan çok sayıdaki köyün yanı sıra, sınırları daraltılarak nahiye haline getirilen Arguvan da Keban Kazası’na dâhil edilmiştir.
19. YÜZYILIN İLK YARISINDA KEBAN KÖYLERİNİN İDARİ VE DEMOGRAFİK YAPISI